Carotid artery intima-media thickness in patients with acute ischemic stroke and its correlation with risk factors for atherosclerosis and/or stroke - Shovan Kumar Das (Asian Journal of Medical Sciences, 2014)
Introduction: Stroke is the second leading cause of mortality worldwide. Ischemic stroke is more prevalent than hemorrhagic stroke and atherosclerosis is the major cause of ischemic stroke. The increased carotid artery intima-media thickness (CIMT) is considered to be useful indicator of early atherosclerosis. So, this study was aimed to correlate the relationship between atherosclerotic risk factors and intima-media thickness of carotid artery in patients with acute ischemic stroke.